A deep dive into shrimp allergy: clinical spectrum of shrimp allergy in a Tunisian pilot study - Krir, Dhouha; Zamali, Imen; Galai, Yousr; Ben Hmid, Ahlem; Ben Sghaier, Ines; Nasri, Yosra; Kebaier, Hayet; Louzir, Hechmi; Ben Alaya Bouafif, Nissaf; Ben Ahmed, Mélika; Samoud, Samar (Frontiers in Allergy, 2025)
Shrimp allergy has emerged as a growing health concern in Tunisia, likely due to changing dietary habits. This study aimed to characterize the clinical features of shrimp-allergic patients and investigate potential cross-reactivity with house dust mites (HDMs) and snails using in vitro diagnostic methods. Thirty-one patients with a self-reported history of shrimp allergy were referred to the Clinical Immunology Department of the Pasteur Institute of Tunis. Total IgE and Serum-specific IgE (sIgE) levels to shrimp, snail, and HDMs, as well as recombinant allergens rPen a1 and rDer p10, were measured using the ImmunoCAP® immunoassay. The study population consisted mainly of young adults [mean age: 15.5 years (10–27.2)], with a male-to-female ratio of 1.4. The most common symptoms were oropharyngeal pruritus and urticaria. Shrimp allergy was confirmed in 54.8% of patients, with a median sIgE titer of 0.18 [0.03–28.8] kUA/L. Among these patients, 58.8% exhibited cross-reactivity, predominantly with snails [median sIgE: 3.07 (0.04–16.85) kUA/L]. Among shrimp-allergic patients, 70.5% tested positive for rPen a1 [median sIgE: 28.42 (5.78–51.05) kUA/L], while 58.8% were positive for rDer p10 (median sIgE: 0.56 [5 × 10−5–87.95] kUA/L). The median total IgE level was 297 [158.6–475] IU/ml, significantly higher in shrimp-allergic patients (p = 0.005). The median shrimp sIgE/total IgE ratio was 0.001 [0–0.069], also significantly elevated in shrimp-sensitized individuals (p = 0.005). Multivariable analysis showed significant correlations between total IgE and shrimp sIgE, rPen a1, and rDer p10 levels (p = 0.043, p = 0.045, p = 0.043, respectively), while no correlation was found with d1 or snail sIgE after adjusting for age. rDer p10 and f24 were the strongest predictors of sIgE to snail, with standardized coefficients of 8.785 and −5.028, respectively. However, these associations did not reach statistical significance. This study underscores the critical role of tropomyosin as a primary allergen in shrimp allergy in Tunisia, highlighting its importance in immunodiagnosis and its strong association with HDMs and snail sensitization. Further research is needed to explore HDMs sensitization in patients who are negative for rPen a1 and rDer p10.